An Examination of the Most Recent Episode of Molly Use among College Students. (April 2017) - Stamates, Amy L.; Linden-Carmichael, Ashley N.; Sheehan, Brynn E.; Preonas, Peter D.; Lau-Barraco, Cathy
The current study examined event-level characteristics (e.g., contextual factors, risk behaviors) during the most recent episode of Molly use among a sample of college students who reported previously using Molly. Participants ( N = 151; 66.7% female) were drinkers aged 18 to 25 years. Data were collected from October to November 2014, February to April 2015, and September to November 2015. Participants completed measures regarding typical Molly use and items related to context and behaviors during their most recent episode of Molly use. Findings revealed that our sample most commonly reported using Molly earlier in the evening while hanging out with friends or at a party. In addition, sexual and other drug use behaviors commonly occurred when using Molly. Findings provide preliminary information in guiding future work exploring Molly use and potential substance-related issues associated with the context of when and how Molly is consumed.